Soybean potassic fertilization in a Dark-Red Latosol sandy loam - Rosolem, Ciro A.; Nakagawa, João; Machado, José R. (Pesquisa Agropecuaria Brasileira, 2014)
During three years, an experiment was carried out in a Dark-Red Latosol (sandy loam) to study the effects of annual applications of 0, 40, 80, 160 and 240 kg/ha of K2O as potassium chloride and potassium sulphate, applied in the seed rows or spread and incorporated. There was a yield increase due to potassium fertilization since the second year. Maximum yields were associated to potassium levels in the leaves above 1.5% In drier than normal years, the spreading applications led to better results than row applications. There were no differences between potassium sources. A decrease in exchangeable potassium levels in the soil was observed; for this reason, the application of doses bigger than 80 kg/ha of K2O a year was considered necessary to maintain the original potassium level. On the other hand, the fertilization with higher potassium doses led to a significant loss of potassium by leaching.